Metode Penafsiran Sayyid Quthb Mengenai Dimensi Politik dalam Perspektif Ayat-Ayat Madaniyyah pada Kitab Tafsir Fi Zhilal Al-Qur'an - B, Amdahurifky; Raya, Ahmad Thib; Tahir, Muhammad Suaib (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The discourse on the interpretation of the Qur’an related to politics still leaves polemics, especially for intellectuals and academics. The pros and cons of the paradigm still occur whether or not politics or a government system are part of Islam and the Qur'an, and have even entered the realm of their respective discourses. This study will explain an alternative paradigm in explaining the political dimension according to the analysis of Sayyid Qutb's method in his commentary book Fī Zhilāl al-Qur'an based on the perspective of the Madaniyyah verses. This research uses a qualitative approach in the form of a literature review. The method used is the method of interpretation of al-maudhū'ī (theme) by including the explanation through a scientific political approach. The big conclusion that can be drawn from this research is that the basic principles of the Qur'an become the applicable basis for political aspects that put forward substantive values and drive universal humanist passions. The term is also referred to as the humanist substantive expression of harakī rabbanī. The operational steps are described in the analytical model of Sayyid Qutb's method in his interpretation of the political dimension, especially with regard to the Madaniyyah verses. The correlation elements are taken based on aspects of political science which became an agreement between political scientists in April 1952 in Cambridge (England).